2013
DOI: 10.3390/ma6093840
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Orthophosphate-Based Bioceramics

Abstract: Various types of grafts have been traditionally used to restore damaged bones. In the late 1960s, a strong interest was raised in studying ceramics as potential bone grafts due to their biomechanical properties. A bit later, such synthetic biomaterials were called bioceramics. In principle, bioceramics can be prepared from diverse materials but this review is limited to calcium orthophosphate-based formulations only, which possess the specific advantages due to the chemical similarity to mammalian bones and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(170 citation statements)
references
References 883 publications
(1,479 reference statements)
1
164
1
4
Order By: Relevance
“…Even though use of CaP based nanoparticles as carriers for intracellular delivery of nucleic acids has been explored for 40 years, the inherent osteogenic effect of calcium and phosphate ions released from such particles has not been considered in the majority of the studies. This is despite the fact that several studies have separately reported the osteoinductive properties of CaP based agglomerates and bulk scaffolding materials 26,27,59 .…”
Section: Discussionmentioning
confidence: 97%
“…Even though use of CaP based nanoparticles as carriers for intracellular delivery of nucleic acids has been explored for 40 years, the inherent osteogenic effect of calcium and phosphate ions released from such particles has not been considered in the majority of the studies. This is despite the fact that several studies have separately reported the osteoinductive properties of CaP based agglomerates and bulk scaffolding materials 26,27,59 .…”
Section: Discussionmentioning
confidence: 97%
“…70 Apatitebased materials are extensively used as bone filler/ grafts. [148][149][150] This is why many drugdelivery systems designed for bonedisease treatment are based on hydroxyapatite. For instance, hydroxyapatite/cisplatin drugdelivery systems were obtained and tested as delivery systems of different platinum complexes.…”
Section: 137mentioning
confidence: 99%
“…More than two million bone graft procedures are performed annually worldwide, of which almost 1.6 million bone grafts are performed in the USA alone [1,2]. In 2010, revenue generated from the use of allogeneic and alloplastic bone graft substitutes was approximately US$1.3 billion in the USA, and is expected to rise to US$2.3 billion by the end of 2017 [3,4]. The standard of care treatment for critical size bone defects is vascularized autographs.…”
Section: Bone Tissue Engineering (Bte)mentioning
confidence: 99%